PERBAIKAN METODE KERJA PADA PROSES SET UP UNTUK MENINGKATKAN PRODUKTIVITAS MARCHINING GATE VALVE DI PT. CAMERON SYSTEMS BATAM - Refdilzon Yasra; Nilda Tri Putri; M. Rozaq M. Rozaq (Universitas Riau Kepulauan, 2021)
PT. Cameron System Batam is a manufacturing company that produces oil and gas equipment. In carrying out the production process the company uses a make to order system where there are many types of product models that are manufacture in varying quantities according to customer demand. Presently the the company direct hours productivity is below the target. Major contributed by Department machining at low productivity direct hours, as reported in the last 6 months production report direct hours productivity. One caused of low direct hour productivity is time for set up machine out of control. The research conducted with objective to determine the standard time required for Set up time and improve the work methods provided to increase the direct hour productivity at Department Machining. Shop floor observation required toidentify the activity and constraint face during the set-up processes. Data observation collected using the statistical method uji keseragaman data and uji kecukupan data. Problem and Process activity identify with Operation process chart, flow process chart and man-machine chart. Man-machine Chart result the time required for the set-up processes is 82 minutes with workload for Man (97.6%) and Manchine (2.4%) that’s show uneven workload. Derived from Flow process chart identify the unproductive activity. Analyze the data and information from process chart using the Fishbone diagram to find the possible cause and identify the improvement using the FMEA method improvement priorities. Base on the FMEA analysis result with highest RPN will be use for priorities improvement activity where the result are Key Fixture manual (40), No set up activity during the machine running (30), Attitude (30), no scale measurement available (30), Lack of awareness (27) and baut (t-daslot) jam (24). Perform the simulation by ploting the data improved from analysis result to the man-machin chart, flow process chart results the standar time for set up is 86 minutes where the workload between man (98%) and Machine (85%). It shown that workload even/ balance and the utilization of the machine increase from 2.4% to 85% it will increase the direct hours and improve the direct hours productivity